2005
DOI: 10.5507/bp.2005.044
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial asthma and Chlamydia pneumoniae antibodies in children aged 4-8 years in Olomouc district

Abstract: BACKGROUND. Although several studies have demonstrated an association between infection with Chlamydia pneumoniae and asthma, these were mainly limited to exacerbation of symptoms in adults with known asthma OBJECTIVE. We investigated the role of C. pneumoniae infection in l49 atopic children with chronic cough and asthma, comparing them with 241 control non-atopic subjects presenting at Olomouc hospital between 1999 and 2003 with non-specific symptoms (temperature above normal (subfebrile), abdominal pain, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Ten pediatric asthma studies from 7 countries met inclusion criteria (Table 1) [12][13][14][15][16][17][18][19][20][21]. Nine studies reported peripheral blood biomarkers (serology in 8, culture in 1) and 1 reported on nasal and/or induced sputum specimens.…”
Section: Updated Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten pediatric asthma studies from 7 countries met inclusion criteria (Table 1) [12][13][14][15][16][17][18][19][20][21]. Nine studies reported peripheral blood biomarkers (serology in 8, culture in 1) and 1 reported on nasal and/or induced sputum specimens.…”
Section: Updated Systematic Reviewmentioning
confidence: 99%
“…Another positive study reported that Cp biomarker positivity was associated with non-atopic asthma [14]. The fifth positive study compared atopic asthma with non-atopic controls, raising the possibility of confounding by atopic status [13]. Of the five studies reporting no significant biomarker association with chronic asthma, one reported a positive association of Cp IgM and acute exacerbations (P = 0.03) [16], and another found a positive association of Cp IgA and asthma in the subgroup…”
Section: Updated Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation